Church polity and politics in the British Atlantic world, c.1635-66 - Vernon, Elliot; Powell, Hunter (Politics, culture and society in early modern Britain, 2020)
Introduction : church polity and politics in the British Atlantic world, c.1635-66 / Eliot Vernon -- 'From the apostles' time' : the polity of the British Episcopal churches, 1603-62 / Benjamin M. Guyer -- Peers, pastors and the particular church : the failure of congregational ideas in the Mersey Basin region, 1636-41 / James Mawdesley -- 'One of the least things in religion' : the Welsh experience of church polity, 1640-60 / Stephen K. Roberts -- Polity, discipline and theology : the importance of the covenant in Scottish Presbyterianism, 1560-c.1700 / R. Scott Spurlock -- Presbyterian ecclesiologies at the Westminster Assembly / Chad Van Dixhoorn -- 'They agree not in opinion among themselves' : two-kingdoms theory, Erastianism, and the Westminster Assembly debate on church and state, c.1641-48 / Eliot Vernon -- The New England way reconsidered : an exploration of church poity and the governance of the region's churches / Francis J. Bremer -- The association movement and the politics of church settlement during the interregnum / Joel Halcomb -- Polity and peacemaking : to what extent was Richard Baxter a congregationalist? / Tim Cooper -- 'Promote, protect, prosecute' : the congregationalist divines and the establishment of church and magistrate in Cromwellian England / Hunter Powell -- The restoration episcopate and the interregnum : autobiography, suffering and professions of faith / Sarah Ward Clavier.